Efektivitas Media Business Map dalam Meningkatkan Kompetensi Berwirausaha Siswa SMK - Yudiono, Udik (Jurnal Pendidikan Ekonomi Undiksha, 2020)
The purpose of this study was to analyze the effectiveness of application-based business map media as an effort to maximize student competence in making business plans because it is through a business map. The data analysis method in this research is quantitative descriptive. Where the authors will test the effectiveness of the application of business map media in Creative Products and Entrepreneurship subjects in increasing the entrepreneurial competence of vocational students. The effectiveness test uses the benchmark value of g (gain) where effectiveness is obtained from the average gain of students' entrepreneurial competency assessments through confirmation of the worksheets before treatment (pre-test) and after treatment (post-test). The results showed that the media business map was effective in improving students 'entrepreneurial competence, especially in terms of exploring ideas to utilize local potential into superior products that had high selling value, able to improve students' skills in business planning and product evaluation, which was able to foster hard work attitudes, creative and innovative people